Need help with a calc question.?

Attachment image

2 Answers

Relevance
  • 2 months ago

    f(x) = 5cos(x) - 6sin(x)

    F(x) = 5sin(x) - 6[- cos(x)]

     F(x) = 5sin(x) + 6cos(x) + C

    when F(0) = 6

    6 = 5sin(0) + 6cos(0) + C

     6 = 5(0) + 6(1) + C

    6 = 6 + C

    6 - 6 = C

    C = 0

    Therefore

    F(x) = 5sin(x) + 6cos(x) answer// 

    • Login to reply the answers
  • F(x) = 5 * sin(x) + 6 * cos(x) + C

    F(0) = 6

    6 = 5 * sin(0) + 6 * cos(0) + C

    6 = 5 * 0 + 6 * 1 + C

    6 = 6 + C

    0 = C

    F(x) = 5 * sin(x) + 6 * cos(x)

    • Login to reply the answers
Still have questions? Get your answers by asking now.